Potential of Weed As Raw Material for Animal Feed on The Integration of Cattle with Coconut Plantations - I Ketut Ngawit; Nihla Farida (Jurnal Penelitian Pendidikan IPA, 2022)
Constraints on the use of forage for animal feed in smallholder coconut plantations are product availability and chemical composition of nutrients that are lacking and their production potential is low. The reason for this is that the soil under the shade of coconut is not managed intensively. The aim of the study was to evaluate the management of coconut shaded soils based on their ability to increase the potential of forage products and their capacity for raising cattle. The results showed that the production of forage products as raw material for animal feed was the best obtained in the system of planting patterns of sweet corn-long beans-fallow and long beans-sweet corn-fallow. The cropping pattern found 5 species of weeds in the Poaceae family, 4 species of broadleaf weeds and 2 species of puzzles with a palatable level in the category of favored to very favored with an inedible weight percentage of 75.431–98.732%. The Poaceae weed family gave the highest contribution to the total forage production per hectare, which was 8.72 kw ha-1 day-1. While the lowest of broadleaf weeds and puzzles in the system of long bean-sawley-fallow cropping pattern was 1.22 kw ha-1 day-1 and the mustard-longbean-fallow cropping pattern was 1.31 kw ha-1 day-1. The carrying capacity of coconut shaded soil for raising cattle, before being managed was 0.83 ST ha-1-1.52 ST ha-1, after being managed it increased significantly, especially in the sweet corn-longbean-fallow and longbean cropping system. - fallow sweet corn to 2.612 ST ha-1 – 3.87 ST ha-1